Retrospective evaluation of patients diagnosed with childhood (cutaneous) mastocytosis: tü rkiye childhood mastocytosis study group multicenter study - Ozdemir, O.; Dikici, U.; Onata, E. Tusuz; Cogurlu, Mt.; Ozanli, I.; Aydogan, M.; Yakici, N. (Wiley, 2025)
[Abstract Not Available]
European-Academy-of-Allergy-and-Clinical-Immunology (EAACI) Congress -- JUN 13-16, 2025 -- Glasgow, SCOTLAND